Effect of calcium gluconate, calcium lactate, and urea on the kinetics of self-healing in mortars. (30th December 2017) - Ducasse-Lapeyrusse, Jean; Gagné, Richard; Lors, Christine; Damidot, Denis
Highlights: Crack impregnation with calcium lactate increases the self-healing kinetics. Crack impregnation with calcium gluconate increases the self-healing kinetics. Impregnation increases the availability of calcium and carbonate ions. Thick and compact layers of calcite and ettringite in large cracks (>150 μm). Abstract: Bacteria-based healing of cracks remaining in self-healed concrete is under development to improve durability by allowing the healing of large cracks. The objective of this research was to assess the effect of several chemical compounds (called precursors) in particular calcium gluconate, calcium lactate and urea, that could first, enhance the intensity of self-healing and second, serve as nutrients at later ages for either autogenous bacteria or bacteria subsequently added by spraying the concrete surface with a bacterial suspension. Selected solutions containing precursors were used to saturate single cracks of known geometry in mortar specimens. Airflow measurements were used to monitor the healing process and to compare the kinetics of the self-healing between precursor-saturated cracks and non-precursor-saturated cracks. The 24 h immersion of fresh cracks in mortars in calcium lactate or calcium gluconate solutions increased the self-healing kinetics for large cracks. This could increase the availability of calcium ions and carbonate ions, which are the main reagents for the formation of healing products. The higher initial availability of these reagents is confirmed by the rapid decrease of the apparent opening during the first month. The internal crack surfaces were covered with a thick, compact layer of healing products, mainly composed of calcite and ettringite.